2022
DOI: 10.1088/1741-2552/ac65b2
|View full text |Cite
|
Sign up to set email alerts
|

Ethical implications of visual neuroprostheses—a systematic review

Abstract: Objective. The aim of this review was to systematically identify the ethical implications of visual neuroprostheses. Approach. A systematic search was performed in both PubMed and Embase using a search string that combined synonyms for visual neuroprostheses, brain–computer interfaces (BCIs), cochlear implants (CIs), and ethics. We chose to include literature on BCIs and CIs, because of their ethically relavant similarities and functional parallels with visual neuroprostheses. Main results. We included 84 arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…The conspicuous use of these devices could make the user's medical problem more apparent or even the user can be treated by society as a 'cyborg' [ 27 ]. Additionally, the use of BCIs for medical purposes and, even more so, the use of BCIs for commercial purposes can influence social norms [ 28 ] of what is considered normal.…”
Section: Reviewmentioning
confidence: 99%
“…The conspicuous use of these devices could make the user's medical problem more apparent or even the user can be treated by society as a 'cyborg' [ 27 ]. Additionally, the use of BCIs for medical purposes and, even more so, the use of BCIs for commercial purposes can influence social norms [ 28 ] of what is considered normal.…”
Section: Reviewmentioning
confidence: 99%
“…Kenji et al [206] present the potential risks of AI and neurotechnology, including intentional misuse, unintended side effects, and loss of control, as well as how these technologies can be managed to minimize undesirable outcomes. van Velthoven et al [33] identify 169 ethical implications, which should be considered in the early process of technological development, and categorize them into several themes, including benefits for health and well-being, harm and risk, societal effects, and regulation and governance. A major conundrum posed in this regard is to assess whether new rights must be established specifically, as well as the adequacy of the existing laws on the protection of human rights [26,32,35].…”
Section: Neurotechnologymentioning
confidence: 99%
“…This scholarship describes them as being largely not for the collective advantage of humans apart from their sounding noble goals, focusing on the serious concerns and controversies related to their commercial and governance uses beyond the medical and health application domains. While this argument continues to be counterclaimed by the advocates of hybrid intelligence and other controversial intellectual movements, numerous studies have recently revealed a plethora of risks and negative implications of neurotechnology and nanobiotechnology in various domains, including smart cities, XR, computational intelligence, algorithmic governance, security, surveillance, biometrics, medicine, and public healthcare (e.g., [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]). Most of these application domains are associated with the Metaverse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These technological advancements are paired with ethical questions. In the ethical literature, concerns about autonomy, informed consent, participant selection in clinical research, responsibility for actions, privacy and data-security, potential surgical risks and questions regarding costs and accessibility of neurotechnologies have often been described 7 , 8 . The convergence of AI with neurotechnologies expands existing and introduces new ethics concerns, including concerns regarding agency and identity, mental privacy, augmentation, accuracy, transparency and biases 3 , 9 .…”
Section: Introductionmentioning
confidence: 99%